22‐kD growth hormone‐induced nuclear GHR/STAT5/CyclinD1 signaling pathway plays an important role in promoting mesenchymal stem cell proliferation. (5th December 2021) - Zheng, Wei V.; Li, Yaqin; Xu, Yanwei; Zhou, Tao; Li, Dezhi; Cheng, Xianyi; Xiong, Yu; Wang, Shaobin; Chen, Zaizhong
Abstract: Growth hormone (GH) exhibited the important biological activities in the mesenchymal stem cell (MSCs). However, the cellular behavior and properties of GH/GHR in MSCs remain unclear. A series of experiments (such as confocal laser scanning microscope [CLSM] and Western‐blot) were performed to systematically investigate the cellular behavior of GH/GHR in MSCs, and the results showed that GH/GHR not only internalized into the cytoplasm, but also transported into the cell nuclei of MSCs. Furthermore, we studied the molecular mechanism by which GH/GHR internalized into cell, and the results indicated that clathrin plays more important role in the process of GHR internalization. More importantly, it can be found that nuclear‐targeted GHR has the important biological functions in MSCs, which could promote MSCs proliferation. We further revealed the molecular mechanism by which nuclear‐localized GHR regulates MSCs proliferation, and found that nuclear‐targeted GHR enhanced the phosphorylation of STAT5, and the activated STAT5 initiates the transcription of CyclinD1, after which, the complex of CyclinD1 and CDK4 further phosphorylates Rb, and the activated Rb releases E2F1, the released E2F1 ultimately realizes the biological function of GH promoting cell proliferation. In short, in the current study，we used MSCs as a model to study the cellular behavior and properties of GH/GHR, and found that GH/GHR can internalize into cell cytoplasm and transport into the cell nuclei. Further work showed that nuclear GHR could drive cell proliferation via GHR/STAT5/CyclinD1 signaling pathway. The current research has laid an important foundation for further study on the regulatory effect of GH on MSCs.